Distinct and heterogeneous trajectories of self‐perceived cognitive impairment among Asian breast cancer survivors. Issue 4 (1st February 2018) - Ng, Terence; Dorajoo, Sreemanee Raaj; Cheung, Yin Ting; Lam, Yick Ching; Yeo, Hui Ling; Shwe, Maung; Gan, Yan Xiang; Foo, Koon Mian; Loh, Wei‐Jen Kiley; Koo, Si‐Lin; Jain, Amit; Lee, Guek Eng; et al.
Abstract: Objectives: Currently, there are no studies that have established the self‐perceived cognitive trajectories experienced by breast cancer patients (BCPs) post‐chemotherapy. Therefore, we characterized the long‐term trajectory of self‐perceived cognitive function among Asian early‐stage BCPs using the minimal clinically important difference of a subjective measure of cognitive function. Methods: Early‐stage BCPs who received chemotherapy were recruited and assessed at 4 time points: Before chemotherapy initiation (T1), 6 weeks post‐chemotherapy initiation (T2), 12 weeks post‐chemotherapy initiation (T3), and 15‐months post‐chemotherapy initiation (T4). All assessments were performed approximately within 2 weeks post‐chemotherapy. Subjective and objective cognitive function were assessed using Functional Assessment of Cancer Therapy‐Cognitive (version 3) and Headminder™. Results: A total of 166 BCPs were recruited, of whom 131 completed assessment at all time points. Using the minimal clinically important difference of Functional Assessment of Cancer Therapy‐Cognitive, 5 distinct cognitive trajectories were established. Of the 131 patients, 70 (53.4%) did not report any clinically significant cognitive impairment. Twenty‐one (16.0%) patients reported acute cognitive changes during chemotherapy (T2 and/or T3) but not at T4. Forty patients (30.5%) reported clinically significant cognitive impairment at T4, of whom 18 did not report any cognitive impairment at earlier time points. Fifteen (11.5%) patients reported persistent cognitive impairment throughout all time points, while 7 (5.3%) patients reported intermittent cognitive impairment at T2 and T4 but not at T3. Conclusion: This is the first study to establish the existence of heterogeneous cognitive trajectories based on clinically significant thresholds of self‐perceived cognitive impairment. The findings have important implications on the window for screening and management of post‐chemotherapy cognitive impairment.